The Defects and Improvements of the Internal Control Audit in Chinese Universities with respect to the Probabilistic Hesitant Fuzzy Environment. (11th June 2021) - Zhu, Jingjuan; Xu, Ling; Liu, Yunzhong; Zhu, Dawei; Chen, Liangliang
Abstract : This paper analyzes the survey data and qualitative evaluation information of the internal control audit of some universities directly under the Ministry of Education of China (MEC) by using the principal component analysis. The qualitative evaluation information is given by experts and presented by the probabilistic hesitant fuzzy elements. The analysis results show that the internal control audit system and process are not perfect, the professional knowledge and skills of internal auditors in universities are not very adaptable to internal control audit, and the effectiveness of internal control audit management conducted by external firms is not good. These are the three most serious defects of the current internal control audit in universities. The most critical factors influencing the quality of internal control audit in universities are, in order, the difficulty of rational use of the results of internal control audit by universities, the poor support of the leadership for internal control audit, and the insufficient professional knowledge and skills of internal auditors to conduct internal control audit. Thus, this paper proposes that the optimization suggestions for the internal control audit of universities are to establish and improve their internal control audit system and process to continually promote the application of internal control audit results, to increase the degree of attention of the leadership, and to strengthen the construction of the internal audit teams.